Optimal Combinations of Income Tax and Subsidies for Education - Geir Haakon Bjertnæs (Statistics Norway, Research Department, 2001)
Nielsen and Sørensen (1997) find that progressive taxation of labour income is optimal when capital income is taxed. This paper shows that their main result still holds when introducing endogenous choice of occupation, individuals with non- pecuniary preferences for one type of occupation, and tuition fees into the model, provided the subsidy rate for tuition in the high skill occupation is not too low. However, a new result in this paper state that efficiency can be reached when labour income tax is proportional and capital income is taxed, provided that the rates of subsidies for tuition are lower than the labour income tax rate.
Keywords: H21; H24; 330; Optimal income taxation; Human capital investments; Subsidies for tuition; Skill formation